Can Money Buy Advocacy? The Moderating Role of Referral Programs in B2B SAAS - Muh Arif Mahfudin; Ngatno Ngatno (Cv. Syntax Corporation Indonesia, 2026)
The cost of acquiring new customers in SaaS companies requires companies to have an effective strategy. A strategy that is often applied is a referral program, although its effectiveness is unclear. This study discusses customer advocacy influenced by Trust, Security, Customer Satisfaction and Ease of Use in the financial SaaS environment. This study extends the UTAUT framework by integrating the moderating role of the Referral Program on the relationship between driving variables and advocacy. Respondents were 202 from